Solid acid catalyst as well as preparation method and application thereof
By introducing nitrogen-containing compounds and furfural in the synthesis process of solid acid catalysts, a solid acid catalyst with high catalytic activity and stability is solved, and the service life of the catalyst is extended.
Patent Information
- Application Number
- CN202411619994.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The sulfonate stability of existing solid acid catalysts is insufficient, resulting in a gradual decrease in the catalytic effect over the use time.
When synthesizing a solid acid catalyst, a nitrogen-containing compound and furfural are introduced, and a precursor is formed by reacting with potassium persulfate in aqueous H2SO4 solution, and then reacting with concentrated sulfuric acid in n-heptane to prepare a solid acid catalyst with high catalytic activity and stability.
By introducing nitrogen-containing groups, the stability of the sulfonate is enhanced, the service life of the solid acid catalyst is extended, and its catalytic activity is improved.
Smart Images

Figure CN119702076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a solid acid catalyst and a preparation method and application thereof. Background Art
[0002] The catalytic effect of commercial solid acid catalysts is comparable to that of sulfuric acid. However, due to the insufficient stability of the sulfonate group of the solid acid catalyst, the catalytic effect of the solid acid catalyst will gradually decrease with the use time.
[0003] In order to enhance the stability of the sulfonate group of the solid acid catalyst, since the sulfonate group is a strong electron-withdrawing group, a nitrogen-containing substance that provides electrons is added during the synthesis of the solid acid catalyst to enhance its stability.
[0004] The solid acid catalyst synthesized by this method has more Bronsted acid sites (B acid) and Lewis acid sites (L acid), which means that the solid acid catalyst can catalyze the esterification reaction of acetic acid and methanol as well as the polymerization of lactic acid, and has high research value. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a solid acid catalyst.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions, including:
[0009] The nitrogen-containing compound and furfural are dissolved in an aqueous H2SO4 solution, potassium persulfate is added for stirring reaction, and the solid precipitate is recovered by filtration, washed, and vacuum dried to obtain a precursor;
[0010] The precursor is dispersed in n-heptane, concentrated sulfuric acid is added, and the reaction is stirred. After the reaction is completed, the temperature is cooled to room temperature, filtered, washed, and vacuum dried to obtain a solid acid catalyst.
[0011] As a preferred embodiment of the method for preparing the solid acid catalyst of the present invention, the nitrogen-containing compound comprises one or more of m-aminobenzenesulfonic acid, melamine and ethylenediamine.
[0012] As a preferred embodiment of the preparation method of the solid acid catalyst of the present invention, the molar ratio of the nitrogen-containing compound to furfural is 1:5-20; and the concentration of the H2SO4 aqueous solution is 0.1-5 mol / L.
[0013] As a preferred embodiment of the method for preparing the solid acid catalyst of the present invention, the stirring reaction is carried out at a temperature of 90 to 95° C. and a reaction time of 6 to 24 hours.
[0014] As a preferred embodiment of the method for preparing the solid acid catalyst of the present invention, the mass ratio of the sulfuric acid to the precursor is 10-24:1; the mass volume ratio of the precursor to n-heptane is 1-4 g:20 mL.
[0015] As a preferred embodiment of the preparation method of the solid acid catalyst of the present invention, the washing step is firstly washing with ethyl acetate for multiple times and then washing with a large amount of water to adjust the pH to neutral; the vacuum drying step is performed at a temperature of 50 to 90°C, a vacuum degree of 0.5 to 0.1 MPa and a drying time of 6 to 18 hours.
[0016] Another object of the present invention is to overcome the deficiencies in the prior art and provide a solid acid catalyst
[0017] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a solid acid catalyst, wherein the application includes the preparation of polylactic acid and catalytic esterification reaction.
[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing polylactic acid, comprising:
[0019] The lactic acid and the solid acid catalyst are stirred and mixed, and a prepolymerization reaction is carried out at 120-160° C. and 0.01-0.05 MPa in a vacuum environment for 6-18 hours to obtain a prepolymer; and a final polymerization reaction is carried out at 170-200° C. and 0.05-0.1 MPa for 6-18 hours to obtain polylactic acid;
[0020] The addition amount of the solid acid catalyst is 0.1-1%.
[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing methyl acetate, comprising:
[0022] Add the solid acid catalyst and methanol to acetic acid at 70-90° C., and continue stirring at a speed of 200-500 rpm for esterification reaction for 1-3 hours to obtain methyl acetate;
[0023] Wherein, the ratio of acetic acid, solid acid catalyst and methanol is 1-2:0.02-0.12:1.
[0024] Beneficial effects of the present invention:
[0025] (1) The solid acid catalyst prepared by the present invention has high catalytic activity and stability.
[0026] (2) The preparation method provided by the present invention introduces a nitrogen-containing group during the solid acid synthesis process, thereby enhancing the stability of the sulfonate group of the sulfonated resin, making the sulfonate group less likely to fall off, and extending the service life of the solid acid catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0028] Figure 1 The infrared spectra of [AMSA-PFA], [AMSA-PFA]H2SO4, [PME-PFA]H2SO4 and [EDA-PFA]H2SO4 prepared in the present invention. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0032] The raw materials used in the present invention are all commercially available unless otherwise specified.
[0033] Example 1
[0034] This embodiment provides a method for preparing a solid acid catalyst, specifically:
[0035] 0.012 mol of m-aminobenzenesulfonic acid (2.078 g) and 0.12 mol of furfural (10 mL, i.e., the molar ratio of m-aminobenzenesulfonic acid to furfural is 1:10) were added to 20 mL of H2SO4 aqueous solution (1 mol / L) and mixed well, and then 0.3 g of potassium persulfate was added and stirred continuously in a 90°C oil bath for 12 h. The obtained solid was filtered and recovered, and then washed with ethanol, ethyl acetate, water, etc. for multiple times to ensure that the reactants were completely removed. Subsequently, vacuum drying was performed at 70°C and 0.1 MPa for 12 h to improve the purity and stability of the obtained [AMSA-PFA] precursor.
[0036] Weigh 2.5g of [AMSA-PFA] precursor and disperse it in 20mL of n-heptane, then add 46g of concentrated sulfuric acid, heat and stir at 95°C for 12h. After the reaction is completed, pour it into a beaker filled with a large amount of deionized water, wait for the solution temperature to drop to room temperature, filter it, then wash it with ethyl acetate several times, and then wash the solid with a large amount of water until the pH is neutral. Finally, remove water and ethyl acetate in a vacuum at 70°C to obtain a solid acid catalyst [AMSA-PFA] H2SO4.
[0037] Example 2
[0038] The difference between this embodiment and embodiment 1 is that the mass of m-aminobenzenesulfonic acid is adjusted to 0.006 mol (1.039 g), that is, the molar ratio of m-aminobenzenesulfonic acid to furfural is 1:20, and the rest of the preparation process is the same as that of embodiment 1 to obtain a solid acid catalyst.
[0039] Example 3
[0040] The difference between this embodiment and embodiment 1 is that the mass of m-aminobenzenesulfonic acid is adjusted to 0.024 mol (4.156 g), that is, the molar ratio of m-aminobenzenesulfonic acid to furfural is 1:5, and the rest of the preparation process is the same as that of embodiment 1 to obtain a solid acid catalyst.
[0041] Embodiments 4 to 6
[0042] The difference between this embodiment and embodiments 1 to 3 is that the type of nitrogen-containing compound is adjusted to melamine, and the rest of the preparation process is the same as that of embodiments 1 to 3 to prepare a solid acid catalyst [PME-PFA] H2SO4. Specifically, 0.012 mol, 0.006 mol, and 0.024 mol of melamine and furfural are weighed and mixed respectively.
[0043] Embodiments 7 to 9
[0044] The difference between this embodiment and embodiments 1 to 3 is that the type of nitrogen-containing compound is adjusted to ethylenediamine, and the rest of the preparation process is the same as that of embodiments 1 to 3 to prepare a solid acid catalyst [EDA-PFA] H2SO4. Specifically, 0.012 mol, 0.006 mol, and 0.024 mol of ethylenediamine are weighed and mixed with furfural respectively.
[0045] Figure 1 The infrared spectra of [AMSA-PFA], [AMSA-PFA]H2SO4, [PME-PFA]H2SO4 and [EDA-PFA]H2SO4 prepared by the present invention are shown in Figure 1. It can be seen that the method of the present invention successfully prepares the target product.
[0046] The solid acid catalysts prepared in Examples 1 to 9 above were applied to polymerization reaction to prepare polylactic acid and esterification reaction to prepare methyl acetate in the following manner.
[0047] Preparation of polylactic acid (polymerization reaction): 50g of lactic acid and 0.25wt% of solid acid catalyst were stirred and mixed, and prepolymerized for 12h at 140℃ and 0.05MPa vacuum; the temperature was raised to 190℃, the vacuum was raised to 0.1MPa, and the final polymerization was carried out for 12h to obtain polylactic acid. The molecular weight of polylactic acid was detected by GPC gel chromatography. Parameters: The GPC gel chromatograph was Agilent 1260 produced in the United States, the separation column was a guard column + PLgel MIXED-B LS 300X7.5mm two columns in series, the detector was Refractive Index, the temperature was 35℃, the mobile phase was chloroform, and the flow rate was 1ml / min.
[0048] Preparation of methyl acetate (esterification reaction): 30 g of acetic acid was heated to 80° C., 2.4 g of a solid acid catalyst and 10 g of methanol were added, and the reaction was continued under stirring at 350 rpm for 2 h to obtain methyl acetate and water.
[0049] Analysis of esterification products: The classic reaction of acetic acid and methanol produces methyl acetate and water as the main products. Therefore, the experiment characterizes the progress of the experiment by detecting the decrease in the amount of acetic acid and the increase in the amount of methyl acetate, and provides data support for subsequent calculations.
[0050] The gas chromatograph used was GC-3420A produced by North Rayleigh, the separation column used was a capillary column, the column parameters were 30m*0.32mm*0.50μm, the detector was a hydrogen flame ionization detector, the initial column temperature was 80℃, the injector temperature was 220℃, the detector temperature was 250℃, and the temperature program was kept at 80℃ for 2min, then raised to 200℃ at a rate of 30℃ / min, and kept for 5min after reaching 200℃. During the experimental preparation, a mixed liquid of methyl acetate, methanol, and acetic acid in a ratio of 15:3:1 was prepared, and the mixed liquid was taken and analyzed by gas chromatography to calibrate the peak time of each component. At the beginning of the reaction, the pipette was adjusted to 250μL, the sample was quickly transferred, the sample was placed and quickly transferred to the chromatographic chamber, and the content ratio was tested by gas chromatography. During the reaction, a sample was taken every 20min and quickly transferred to the chromatographic chamber for gas chromatography analysis to test the content ratio of each component. During gas chromatography analysis, rinse the needle repeatedly for more than 8 times, and draw 0.6μL of the liquid to be tested when sampling. From sampling from the three-necked flask to injecting into the chromatograph for chromatographic analysis, the total time should be controlled to be no more than 1 minute to control the accuracy of the test.
[0051] Stability test of sulfonic acid (-SO3H) group: Take 30mL acetic acid and 1.5g catalyst and heat at 115℃ with vigorous stirring, and connect an external condenser to reflux for 24h and 48h, and take 2.5mL of each sample and separate the solid and liquid in a centrifuge tube. The color change of the liquid solution is visually observed, and the content of sulfate (mg / L) is detected by ion chromatography.
[0052] The test results are shown in Table 1.
[0053] Table 1
[0054]
[0055] Note: “-” in the table means no stability test was conducted.
[0056] It can be seen from the above table that adjusting the molar ratio of nitrogen-containing compounds to furfural has a significant effect on the performance of the solid acid catalyst. This is because too low a ratio of nitrogen-containing compounds will lead to reduced stability of the sulfonate group, and too high a ratio will cause the nitrogen-containing compounds to occupy the active sites of the sulfonate group. According to the results in the above table, the best technical effect can be obtained when the molar ratio of nitrogen-containing compounds to furfural in the present invention is 1:10.
[0057] It can be seen from the above table that adjusting the type of nitrogen-containing compound has a significant effect on the performance of the solid acid catalyst. This is because the nitrogen-containing substance containing sulfonate groups can not only provide electrons to stabilize the sulfonate groups, but also provide sulfonate active sites. According to the results in the above table, the best technical effect can be obtained when the nitrogen-containing compound in the present invention is m-aminobenzenesulfonic acid.
[0058] Comparative Example 1
[0059] This comparative example provides a method for preparing a solid acid catalyst, specifically:
[0060] Weigh 20g of granular activated carbon that has been washed with water and dried at 115°C to a constant mass, soak it in 120mL of a 15% p-toluenesulfonic acid aqueous solution for 30h, filter it, dry it at 110°C for 5h, and then cool it in a desiccator to obtain a solid catalyst.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 1 is that m-aminobenzenesulfonic acid is not added, and the rest of the preparation process is the same as that of Example 1 to obtain a solid acid catalyst.
[0063] Comparative Example 3
[0064] 0.012 mol of m-aminobenzenesulfonic acid (2.078 g) and 0.12 mol of furfural (10 mL, i.e., the molar ratio of m-aminobenzenesulfonic acid to furfural is 1:10) were added to 20 mL of H2SO4 aqueous solution (1 mol / L) and mixed well, and then 0.3 g of potassium persulfate was added and stirred continuously in a 50°C oil bath for 12 h. The obtained solid was filtered and recovered, and then washed with ethanol, ethyl acetate, water, etc. for multiple times to ensure that the reactants were completely removed. Subsequently, vacuum drying was performed at 30°C and 0.1 MPa for 12 h to improve the purity and stability of the obtained [AMSA-PFA] precursor.
[0065] Weigh 2.5g of [AMSA-PFA] precursor and disperse it in 20mL of n-heptane, then add 46g of concentrated sulfuric acid, heat and stir at 55°C for 12h. After the reaction is completed, pour it into a beaker filled with a large amount of deionized water, wait for the solution temperature to drop to room temperature, filter it, then wash it with ethyl acetate several times, and then wash the solid with a large amount of water until the pH is neutral. Finally, remove water and ethyl acetate in a vacuum at 40°C to obtain a solid acid catalyst [AMSA-PFA] H2SO4.
[0066] Comparative Example 4
[0067] 0.012 mol of m-aminobenzenesulfonic acid (2.078 g) and 0.12 mol of furfural (10 mL, i.e., the molar ratio of m-aminobenzenesulfonic acid to furfural is 1:10) were added to 20 mL of H2SO4 aqueous solution (1 mol / L) and mixed well, and then 0.3 g of potassium persulfate was added and stirred continuously in an oil bath at 110°C for 12 h. The obtained solid was filtered and recovered, and then washed with ethanol, ethyl acetate, water, etc. for multiple times to ensure that the reactants were completely removed. Subsequently, vacuum drying was performed at 100°C and 0.1 MPa for 12 h to improve the purity and stability of the obtained [AMSA-PFA] precursor.
[0068] Weigh 2.5g of [AMSA-PFA] precursor and disperse it in 20mL of n-heptane, then add 46g of concentrated sulfuric acid, heat and stir at 115°C for 12h. After the reaction is completed, pour it into a beaker filled with a large amount of deionized water, filter it after the solution temperature drops to room temperature, then wash it with ethyl acetate several times, and then wash the solid with a large amount of water until the pH is neutral. Finally, remove water and ethyl acetate in a vacuum at 100°C to obtain a solid acid catalyst [AMSA-PFA] H2SO4.
[0069] The performance test of the comparative example was carried out, and the comparison results with those of Example 1 are shown in Table 2.
[0070] Table 2
[0071] Polylactic acid molecular weight Methyl acetate yield (%) Example 1 62145 80.2 Comparative Example 1 28979 76.8 Comparative Example 2 29887 64.5 Comparative Example 3 37889 71.2 Comparative Example 4 38897 74.9
[0072] As can be seen from the above table, the preparation method provided by the present invention introduces a nitrogen-containing group in the solid acid synthesis process, thereby enhancing the stability of the sulfonate group of the sulfonated resin, making the sulfonate group less likely to fall off, thereby extending the service life of the solid acid catalyst, and the prepared solid acid catalyst has a higher catalytic activity.
[0073] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a solid acid catalyst, characterized in that: include, The nitrogen-containing compound and furfural are dissolved in an aqueous H2SO4 solution, potassium persulfate is added for stirring reaction, and the solid precipitate is recovered by filtration, washed, and vacuum dried to obtain a precursor; The precursor is dispersed in n-heptane, concentrated sulfuric acid is added, and the reaction is stirred. After the reaction is completed, the temperature is cooled to room temperature, filtered, washed, and vacuum dried to obtain a solid acid catalyst.
2. The method for preparing a solid acid catalyst as claimed in claim 1, wherein: The nitrogen-containing compound includes one or more of m-aminobenzenesulfonic acid, melamine, and ethylenediamine.
3. The method for preparing a solid acid catalyst as claimed in claim 1, wherein: The molar ratio of the nitrogen-containing compound to furfural is 1:5-20; the concentration of the H2SO4 aqueous solution is 0.1-5 mol / L.
4. The method for preparing a solid acid catalyst as claimed in claim 1, wherein: The stirring reaction, wherein the reaction temperature is 90-95° C., and the reaction time is 6-24 hours.
5. The method for preparing a solid acid catalyst according to claim 1, wherein: The mass ratio of the sulfuric acid to the precursor is 10-24:1; the mass volume ratio of the precursor to n-heptane is 1-4 g:20 mL.
6. The method for preparing a solid acid catalyst according to claim 1, wherein: The washing step includes washing with ethyl acetate for multiple times and then washing with a large amount of water to adjust the pH to neutral. The vacuum drying step includes drying at a temperature of 50 to 90° C., a vacuum degree of 0.5 to 0.1 MPa, and a drying time of 6 to 18 hours.
7. A solid acid catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the solid acid catalyst as claimed in claim 7, characterized in that: The applications include the preparation of polylactic acid and the preparation of methyl acetate.
9. A method for preparing polylactic acid, characterized in that: include, The lactic acid and the solid acid catalyst according to claim 7 are stirred and mixed, and a prepolymerization reaction is carried out at 120-160° C. and 0.01-0.05 MPa in a vacuum environment for 6-18 hours to obtain a prepolymer; and a final polymerization reaction is carried out at 170-200° C. and 0.05-0.1 MPa for 6-18 hours to obtain polylactic acid; The addition amount of the solid acid catalyst is 0.1-1%.
10. A method for preparing methyl acetate, characterized in that: include, Add the solid acid catalyst according to claim 7 and methanol to acetic acid at 70 to 90° C., and continue stirring at a speed of 200 to 500 rpm for esterification reaction for 1 to 3 hours to obtain methyl acetate; Wherein, the ratio of acetic acid, solid acid catalyst and methanol is 1-2:0.02-0.12:1.
Citation Information
Patent Citations
Photocurable resin composition, dry film, cured product and printed wiring board
CN103365084A
Method for sulfonated polyaniline catalytic synthesis of 5-hydroxymethylfurfural from carbohydrates
CN106432145A
Lignosulfonate-based solid acid catalyst and preparation method and application thereof
CN107243360A
Preparation method and application of solid acid catalyst loaded with ionic liquid
CN115106125A
Catalyst for synthesizing tri-fatty glyceride, preparation method of catalyst, tri-fatty glyceride, preparation method of tri-fatty glyceride and application of tri-fatty glyceride
CN115350726A